An Analysis of E-Commerce Adoption for Small and Medium Enterprises in Indonesia - Fahruzzaman, Fauzan; Subriadi, Apol Pribadi (IPTEK Journal of Proceedings Series, 2015)
The amount of small and medium enterprises (SME) is the largest number of business actor in Indonesia. But the contribution of SME is very small compared with large business. Some researchers found that the most influencing factor cause the condition is the use of information technology. May of the SMEs have not seen the power of information technology such as e-commerce. Author uses the qualitative method to gather deep information from informant that unfound in the recent quantitative research. This research will conduct how to implement the e-commerce based on some successful experiences in SME.